2017
DOI: 10.1111/asj.12795
|View full text |Cite
|
Sign up to set email alerts
|

Silage fermentation and ruminal degradation of stylo prepared with lactic acid bacteria and cellulase

Abstract: In order to improve the silage fermentation of stylo (Stylosanthes guianensis) in tropical areas, stylo silages were prepared with commercial additives Lactobacillus plantarum Chikuso-1 (CH1), L. rhamnasus Snow Lact L (SN), Acremonium cellulase (CE) and their combination as SN+CE or CH1 + CE, and the fermentation quality, chemical composition and ruminal degradation of these silages were studied. Stylo silages treated with lactic acid bacteria (LAB) or cellulase, the pH value and NH -N ⁄ total-N were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 27 publications
10
31
3
1
Order By: Relevance
“…Therefore, the addition of ENZ may not have beneficial effects on promoting the propagation of LAB. Previous studies, have suggested that addition of cellulase could improve the fermentation quality by degrading NDF and ADF of tropical crop and by-product silages (Khota et al 2016;Li et al 2017;Wang et al 2019). This result was not evident in our study, this could be attributed to the fibrolytic enzyme activity which depends on the temperature and pH condition (Colombatto et al 2004).…”
Section: Fermentation Quality and Nutritive Valuecontrasting
confidence: 78%
“…Therefore, the addition of ENZ may not have beneficial effects on promoting the propagation of LAB. Previous studies, have suggested that addition of cellulase could improve the fermentation quality by degrading NDF and ADF of tropical crop and by-product silages (Khota et al 2016;Li et al 2017;Wang et al 2019). This result was not evident in our study, this could be attributed to the fibrolytic enzyme activity which depends on the temperature and pH condition (Colombatto et al 2004).…”
Section: Fermentation Quality and Nutritive Valuecontrasting
confidence: 78%
“…The experimental results are in agreement with Li, Zhou, Zi, and Cai (2017) who determined that LAB can improve fermentation quality, chemical composition, and bioavailability (inhibiting protein degradation and promoting fiber degradation), thus having great potential as an additive for bran fermentation. The experimental results are in agreement with Li, Zhou, Zi, and Cai (2017) who determined that LAB can improve fermentation quality, chemical composition, and bioavailability (inhibiting protein degradation and promoting fiber degradation), thus having great potential as an additive for bran fermentation.…”
Section: Content Of Crude Protein Fat Fiber and Their Fractions supporting
confidence: 89%
“…Most of gramineae grasses were low in nutritional value as they have high moisture and fiber content but low protein content. In contrary, legume and foliage normally have low moisture and high protein content (Li, Zhou, Pan et al, ; Li, Zhou, Zi et al, ; Syahniar, Ridla, Jayanegara, & Samsudin, ). Their mixtures as silage have good fermentation quality and balanced nutrients.…”
Section: Discussionmentioning
confidence: 99%